Random lasers : development, characterization and dental image generation - MENDOZA CARREÑO, Sandra Johana (2023)
Random laser (RLS) emerges with great boost in photonic exploration for complex systems studies and biological systems. This thesis addresses the construction, characterization and application of RLS of different gain and dispersion materials, aiming at its use in the optical transillumination system of biological tissues. In addition to being studied random laser emission intensity fluctuations, observing the existence of non-Gaussian statistics of the type Lévy, distribution of Izrailev and breaking replica symmetry using 6G Rhodamine RL with nanoparticles of TiO2. In this thesis the low coherence issuance of the RLs were explored to generate images free of biological tissue blemishes. In the first chapter of this text an introduction to RLs and its applications in the area of biomedical optics is made. The second chapter focuses on the theoretical description of the emission of colloidal and solid state RLs. The third chapter presents the construction and characterization of RLs, with the observation of nonlinear effects and photonic phase transitions on RLs systems. A large set of RL emission spectra were analyzed for statistical analysis of radiation. In the fourth chapter, the use of RL is presented in the transillumination image technique for generation characterization of biological systems. In this case, an organic Pyridine2 dye was used in ethylene glycol with nanoparticles, TiO2 to generate RL with emission in the first biological window (750nm). Experimentally evaluated the coherence of RL emission, with the quantification of laser radiation coherence length (13 μm). The use of RL was first demonstrated in the optical transitional technique for dental tissue image generation. The results indicate that Pyridine2 RL is a source of great potential to generate images of spot free dental fabric in the nearby infrared.